ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERUBAHAN LABA - Ifada, Luluk Muhimatul; Puspitasari, Tiara (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
This study aims to examine and analyze the influence of Current Ratio (CR), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Gross Profit Margin (GPM), and Net Profit Margin (NPM) to changes in earnings in manufacturing companies listed in Indonesia Stock Exchange 2011-2013. A sample of 55 companies were obtained using purposive sampling method with the following criteria: (1) companies listed on the Stock Exchange consistently during 2011-2013; (2) manufacturing company serving the financial statements have been audited; (3) manufacturing company publishes financial statements ended on December 31 for the fiscal year 2011-2013; (4) manufacturing company in rupiah; (5) and manufacturing company that produces positive earnings. Data analysis method used is multiple linear regression method. The result shows that the variables CR, DAR, TATO, GPM and NPM significantly influence changes in earnings